The Poets of Professions and Crafts in the Mamluk Era - Assis.Lect. Saja Jawa Mahde (Journal of College of Education, 2024)
During the Mamluk era, some poets did not have the opportunity to attend the sultans' and princes' gatherings, so they did not receive rewards or gifts. As a result, these poets turned to their crafts, professions, and industries as a means of making a living. They all reflected the nature of their trade or craft in their poetic movements and wrote about various poetic subjects. It was observed that alongside their chosen professions and different industries, these figures did not neglect to pursue the poetic movement of their time and carry the banner of creativity through their instinct, character, and spontaneity.These skilled poets engaged with people and coexisted with them in a simple and easy manner. It is noteworthy that some poets ridiculed their own crafts, criticized them, and displayed disdain for them. Interestingly, at times they praised their crafts and at other times mocked them. Their craft became associated with humiliation and people's contempt for them. Therefore, they strongly desired to abandon their crafts, considering them a cause of their unhappiness and the deterioration of their status. This led them to turn to poetry in search of livelihood. However, their hopes were dashed, and they gained nothing from it to improve their circumstances and conditions. They were given meager rewards and endured humiliation and degradation in their quest for financial support. Nevertheless, they combined their craft with the art of poetry, and we can find in their poems the impact of time on them and their frequent complaints and descriptions of their miserable state. Their distress reached a point where they lamented their ill-fated fortune, which had brought them into this craft.
Keywords: Poetry of the Professions, Complaint, Craftsmanship, Mamluk Era